2011
DOI: 10.1002/pip.1069
|View full text |Cite
|
Sign up to set email alerts
|

Recent results for single‐junction and tandem quantum well solar cells

Abstract: Abstract:We propose and experimentally demonstrate that, contrary to what was thought up to now, an efficient BB84 operation is feasible using the double phase modulator (PM-PM) configuration in frequency-coded quantum key distribution systems without dispersion compensation. This is achieved by exploiting the chromatic dispersion provided by the fiber linking Alice and Bob. Thus, we refer to this system as dispersion supported or as the DS BB84 PM-PM configuration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 46 publications
1
34
1
Order By: Relevance
“…Strain balanced multi-quantum wells (MQW) are an established method for tailoring the absorption edge of III-V solar cells. Research over the last couple of years has addressed the performance as a function of the position of the QWs inside the device, 1,2 their number, 3,4 their composition to keep them strain-balanced, 5 and the effect of background doping on carrier extraction. 6 As a result of these efforts, InGaP/MQW/Ge quantum well devices have attained efficiencies in excess of 40% under concentration 5 and over 30% under air-mass 0 solar spectrum (AM0).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Strain balanced multi-quantum wells (MQW) are an established method for tailoring the absorption edge of III-V solar cells. Research over the last couple of years has addressed the performance as a function of the position of the QWs inside the device, 1,2 their number, 3,4 their composition to keep them strain-balanced, 5 and the effect of background doping on carrier extraction. 6 As a result of these efforts, InGaP/MQW/Ge quantum well devices have attained efficiencies in excess of 40% under concentration 5 and over 30% under air-mass 0 solar spectrum (AM0).…”
mentioning
confidence: 99%
“…Research over the last couple of years has addressed the performance as a function of the position of the QWs inside the device, 1,2 their number, 3,4 their composition to keep them strain-balanced, 5 and the effect of background doping on carrier extraction. 6 As a result of these efforts, InGaP/MQW/Ge quantum well devices have attained efficiencies in excess of 40% under concentration 5 and over 30% under air-mass 0 solar spectrum (AM0). 7 These achievements have required a mastery of the fabrication of strain balanced MQW structures on highly misoriented substrates (typically [100] 6 towards [111]B).…”
mentioning
confidence: 99%
“…For example, strain-balanced quantum wells (QW) or quantum dots (QD) can be used to effectively lower the bandgap, and single-junction cell efficiencies of over 28% under concentration has been achieved via this approach [23].…”
Section: Nanostructures For Bandgap Engineeringmentioning
confidence: 99%
“…As discussed before, for a 3J device with a germanium bottom cell, an optimum band gap combination under AM1.5D solar spectrum at 1000 suns would be around 1.19 eV -1.75 eV for the middle -top cells, respectively (Figure 1). However, Browne et al showed that the optimum bandgap in a QW solar cell was indeed dependent on the quantum efficiency of the QWs, being higher if that efficiency was below certain value 1 . As we will discuss in the next section, although the quantum efficiency (QE) of a MQW structure can reach up to 75%, state of the art MQW solar cells have more often values between 40%-60%.…”
Section: Target Performance For Maximum Efficiencymentioning
confidence: 99%
“…The most successful application of this technique was a GaAs, single junction device with multiple InGaAs/GaAsP quantum wells, that had an efficiency of 28.3% under AM1.5D 416 X, breaking a 20-year long world record for single junction devices 1 . More recent research in this field has already produced dual-junction devices with efficiencies close to their bulk counterparts (30.6% compared to 31.7%).…”
Section: Historic Perspectivementioning
confidence: 99%